Body Waves and Rayleigh Waves Characterization of Sinabung Volcano VT-A Earthquake in June - December 2011 Using Polarization Analysis - FAISAL DAHLAN (NIM : 12313030), EMIRZA
The observation of earth seismic activity requires high accuracy and expertise from the observer. The observation that depends on the observer's subjectivity is difficult to be applied on volcanic earthquake activity, since the signal onset is often hardly visible. Polarization analysis was used in this research as a supporting method in the observation of the volcanic earthquake data. The seismogram data of Sinabung Volcano in June - December 2011 was obtained from PVMBG. The polarization analysis was applied on the recorded data of the VT-A earthquake (deep events) with the calculation of Rectilinearity (RL) parameter and the dot product angle parameter of P and S wave polarization. The obtained time window was later used to identify the dominant frequency and the polarity connection between desired signal and unwanted noise. Polarization analysis was proven to ease the characterization of the duration between body waves, and the arrival time of Rayleigh wave in every VT-A signal. The recorded VT-A earthquake during data research period was categorized as high frequency (HF) earthquake with 6 – 14 Hz and approximately 0,5 – 3,3 seconds difference between P waves’ and S waves’ onset. The pure P waves’ frequency was dominated by 9 – 14 Hz with approximately 0,05 – 2,7 seconds duration. The pure S and Rayleigh wave were dominated by lower frequency, 5 – 10 Hz for the pure S waves with approximately 0,1 – 1 seconds duration of propagation and 5 – 8 Hz for the Rayleigh waves with approximately 1,2 – 4,7 seconds after the onset of P waves. The existence of noise is significant toward the polarization analysis method. The result of the SNR analysis shows that the ideal SNR for research with polarization analysis is above 12 dB.